Evaluating the potential of tree-ring methodology for cross-dating of three annually laminated stalagmites from Zoolithencave (SE Germany) - Riechelmann, Dana; Kluge, Tobias; Frank, Norbert (Quaternary geochronology, 2019)
Three small stalagmites from Zoolithencave (southern Germany) show visible laminae, which consist of a clear and a brownish, pigmented layer pair. This potentially provides the opportunity to construct precise chronologies by counting annual laminae. The growth period of the three stalagmites was constrained by the 14C bomb peak in the youngest part of all three stalagmites and 14C-dating of a piece of charcoal in the consolidated base part of stalagmite Zoo-rez-2. These data suggest an age of AD 1970 for the top laminae and a lower age limit of AD 1973-1682 or AD 1735-1778. Laminae were counted and their thickness determined on scanned thin sections of all stalagmites. On stalagmites Zoo-rez-1 and -2, three tracks were measured near the growth axes, each separated into three sections at prominent anchor laminae (I, II, III). Each section was replicated three times (a, b, c). For Zoo-rez-3, only one track was measured. The total number of laminae counted for Zoo-rez-1 ranges from 138 to 177, for Zoo-rez-2 from 119 to 145, and for Zoo-rez-3 from 159 to 166. The numbers agree well with the range constrained by the bomb peak and the age of the charcoal, which supports the annual origin of the laminae. The replicated measurements of the different tracks as well as the three different tracks on the stalagmites Zoo-rez-1 and -2 were cross-dated using the TSAP-Win® tree-ring software. This software is very useful for cross-dating because it enables to insert or delete missing or false laminae as well as identifying common pattern by shifting the series back and forth in time. However, visual inspection of the thin sections was necessary to confirm detection of missing or false laminae by TSAP-Win®. For all three Zoo-rez speleothems, cross-dating of the mean lamina thickness series was not possible due to a missing common pattern. The cross-dating procedure results in three refined chronologies for the three Zoo-rez stalagmites of ranging from AD 1821-1970 (Zoo-rez-1), AD 1835-1970 (Zoo-rez-2), and AD 1808-1970 (Zoo-rez-3).
Gesehen am 29.01.2020